SOCIAL REHABILITATION OF FAMILIES WITH CHILDREN WITH DISABILITIES THROUGH THE ORGANIZATION OF MUTUAL ASSISTANCE GROUPS - Burenina, Svetlana; Kalinina, Svetlana; Petrash, Elena; Borisov, Boris; Shpak, Alexey (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The article tells about the experience of the state budget institution of social services of the Pskov region "Rehabilitation center for children and adolescents with disabilities" from Velikiye Luki in the rehabilitation of children and adolescents aged 0 to 18 years with disabilities in mental and physical development, ensuring their fullest and timely social adaptation to life in society, family, education and work through the organization of mutual assistance groups. The effectiveness of this form of work with a family raising a child with disabilities is shown by teaching parents to understand their children, identify their abilities and needs for their further development. These theoretical positions were confirmed by experimental work that took place in three stages, including the social project "All together" with an inclusive component, which allowed to develop the huge internal potential of families raising children with disabilities for their more effective rehabilitation.